Prevalence and Hospital Admissions in Patients With Osteogenesis Imperfecta in The Netherlands: A Nationwide Registry Study - Storoni, Silvia; Treurniet, Sanne; Maugeri, Alessandra; Pals, Gerard; van den Aardweg, Joost G.; van der Pas, Stéphanie L.; Elting, Mariet W.; Kloen, Peter; Micha, Dimitra; Eekhoff, Elisabeth Marelise W. (Frontiers in Endocrinology, 2022)
Osteogenesis Imperfecta (OI) is a complex disease caused by genetic alterations in production of collagen type I, and collagen-related proteins. Bone fragility is the most common patient issue, but extraskeletal complications also present an adverse factor in the quality of life and prognosis of patients with OI. However, still little is known about the morbidity and mortality of these patients. The objective of this paper is to determine and describe to what extent OI impacts patients’ life in terms of hospitalization and complications describing the incidence and prevalence of the Dutch cohort of OI patients and the characteristics of their hospital admissions. Information regarding OI patients and their hospital admission was extracted from the Statistics Netherlands Database and matched to the OI Genetics Database of Amsterdam UMC. Hospital admission data was available for 674 OI patients. This OI nationwide registry study shows that the life expectancy of OI patients is adversely affected by the disease. The median annual incidence risk of OI between 1992 and 2019 was 6.5 per 100,000 live births. Furthermore, patients with OI had a 2.9 times higher hospitalization rate compared to the general Dutch population. The highest hospitalization rate ratio of 8.4 was reported in the patient group between 0 and 20 years old. OI type and severity had impact on extraskeletal manifestations, which play a key role in the numerous hospital admissions. More awareness about the impact of OI on patients’ life is needed to improve and implement prevention and follow-up guidelines.